The Identification of Land Use Conflicts and Policy Implications for Donghai County Based on the “Production–Living–Ecological” Functions - Jianying Xiao; Jinjin Dai; Longqian Chen; Yan Song (Land)
The rapid development of urbanization has continuously encroached on people’s living space and ecological space, leading to an imbalance in territorial spatial functions. Identifying potential land use conflicts and optimizing land use structure are conducive to carrying out territorial spatial planning rationally. In this paper, we adopt the suitability assessment method to evaluate the suitability of land for production, living, and ecological functions and then use the land use conflict identification matrix to identify land use conflicts in Donghai County and make relevant suggestions according to the intensity of land use conflicts. The results of this study show the following: (1) the areas of suitable land use zones, strong conflict zones, medium conflict zones, and weak conflict zones in Donghai County are, respectively, 58.83%, 10.62%, 26.31%, and 4.24%. (2) The spatial distribution differences in the different conflict zones could determine the pertinence of conflict mitigation and spatial planning. In the process of the urbanization of Donghai County, ecological environmental protection is still the top priority. (3) It is necessary to economically and intensively use construction land, improving its fine management level. Land use efficiency should be maximized, and the spatial distribution of national territory should be reasonably optimized while strengthening the guiding role of planning. This study addresses land conflicts from the perspective of spatial planning rather than economic behavior. It also provides significant insight into land use layout at the county level, which is exactly what China is exploring in the new era.